INFLUENCE OF NON-FORMAL WORK-RELATED LEARNING ON THE QUALITY OF SERVICE DELIVERY OF COMMUNITY DEVELOPMENT WORKERS IN OYO STATE - OLAWALE-JIMOH, Abimbola Roseline; JIMOH, Teslim Olawale (Ilorin Journal of Education, 2023)
This study examined the influence of work-related learning on the quality of service delivery of community development workers (CDWs) in Oyo State. It identified the non-formal work-related learning acquired by the CDWs, investigated the quality of CDWs‟ service delivery and determined the perception of the executive members of community development associations (CDAs). It also investigated the influence of demographic variables on the quality of CDWs‟ service delivery. The study adopted survey design using multi-stage sampling procedure to select 137 respondents: 113 community development workers (CDWs) and 24 executive members of community development associations (CDAs). Questionnaire and Interview Guide were used to elicit information from the CDWs and executive members of CDAs respectively. Three research questions were answered and one hypothesis was tested. Data were analysed using Chi-square analysis. Findings showed that the CDWs were exposed to non-formal work-related learning on identification of community issues, needs and problems, creating public awareness and mobilization of community members to form CDAs. It showed that the CDWs delivered the following services promptly and regularly: attending and coordinating CDAs meetings, identifying community issues, needs and problems; mobilizing community members to form CDAs. The results also showed that there was no significant influence of demographic variables such as age (χ2 = 2.24, df = 4 p>.05); sex (χ2 = 1.89, df = 2 p>.05); level of education (χ2 = 14.65, df = 8& p>.05); area of specialization (χ2 = 5.85, df = 8 & p>.05) and length of service (χ2 = 2.24, df = 4 & p>.05) on the quality of CDWs‟ service delivery in Oyo State.